Rapid fabrication of perovskite solar cells through intense pulse light annealing of SnO2 and triple cation perovskite thin films. (5th January 2020) - Ghahremani, Amir H.; Martin, Blake; Gupta, Alexander; Bahadur, Jitendra; Ankireddy, Krishnamraju; Druffel, Thad
Abstract: Rapid evolution of perovskite solar cells (PSCs) performance and stability has inclined the research focus towards scalable bulk fabrication through high speed and cost-effective automated methods. For the first time, intense pulsed light (IPL) is utilized to rapidly fabricate efficient PSCs through swift annealing of both the SnO2 electron transport layer (ETL) and mixed triple cation perovskite thin films. The addition of di-iodomethane (CH2 I2 ) alkyl-halide could enhance the PSC efficiency by retarding the crystallization and improving the surface morphology of the perovskite photoactive film through supplying iodine cleaved by ultraviolet energy during IPL process. The maximum efficiency and fill factor of the PSCs fabricated by IPL annealing were 12.56% and 78.3% for the rigid glass-FTO slides, and 7.6% and 64.75% for flexible PET-ITO substrates when processed in the ambient with relative humidity of 60%, respectively. The annealed materials were characterized through Scanning electron microscopy (SEM), UV–Vis, photoluminescence (PL), X-ray diffraction (XRD), and X-ray photoelectron spectroscopy (XPS) techniques. In addition, impedance spectroscopy (IS) and current-voltage measurements were conducted to study the functionality of fabricated cells. Our results delineated the feasibility of sequential step IPL annealing on rapid fabrication of efficient PSCs which is directly applicable for scalable roll-to-roll manufacturing. Graphical abstract: Image 1 Highlights: Sequential step IPL annealing, SnO2, Perovskite film, Perovskite solar cell, Rapid thermal annealing. Di-iodomethane (CH2 I2 ) was shown to be compatible and improve the quality of fabricated films derived from other perovskite chemistries such as mixed triple cation precursors. Pulse count and the heat flux per pulse was shown to play a significant role on SnO2 charge extraction.